Qualidade da informação contábil: um estudo das cooperativas de crédito brasileiras - Diniz, Marcelo Maia (2020)
Credit Unions as agents participating in the financial market, as a financial intermediary, have characteristics similar to those of banks, with regard to accounting and supply of economic and financial products and services, however they have specific regulations and differ from banks in the business objective, not having a profit, but providing services through mutuality to its members. Thus, this research assessed the quality level of accounting information, using proxies as conservatism, persistence of profits and earnings management through provisions for doubtful loans (PCLD), reported in the financial statements of credit unions Brazilian companies. Using models available in the literature for similar companies, such as Ball and Shivakumar (2005) for conservatism analysis, Dechow and Schrand (2004) for profit persistence and Fuji (2004) and Goulart (2007) for earnings management for specific accruals. Annual data from Brazilian credit unions were used, available on the website of the Central Bank of Brazil (BACEN). The collection refers to the period from 2000 to 2018. As a result, it was found that the financial statements of credit unions indicate a more timely behavior of losses than of gains, it was also identified that larger cooperatives are more conservative than smaller ones. As for the persistence of surpluses reported by credit unions, it was found that the proxy is verified for the group of Brazilian cooperatives and that the largest cooperatives have more intensity compared to the smaller ones. As for earnings management by PCLD, it was found that Brazilian credit unions do not show evidence of earnings management with the use of PCLD.